Factors influencing underrepresented geoscientists' decisions to accept or decline faculty job offers in the US - Margaret L. Duffy; Liza Y. Barnes; Christopher D. Wirz; Meghana Ranganathan; Mara A. Freilich; Lyssa M. Freese; Ellen Lalk; Julia Wilcots (Communications Earth & Environment)
Abstract Many geoscience departments in the United States (US) are working to recruit faculty from underrepresented groups. However, there is little information about how hiring practices are perceived by candidates. Here we address this gap by interviewing 19 geoscientists who identify as an underrepresented race, ethnicity, or gender who recently declined a tenure-track faculty job offer in the US about their faculty job searches, with an emphasis on their decisions to accept or decline an offer. We find that many participants experienced hiring practices inconsistent with existing recommendations to increase faculty diversity, and some participants were subject to uncivilized, even potentially discriminatory, practices. Therefore, we leverage our results to provide actionable recommendations for improving faculty recruitment efforts. We highlight that departments may doubly benefit from improving their culture: in addition to benefiting current members, it may also help with recruitment. Overall, our findings emphasize the need for continued evaluation of faculty hiring practices.